Integrative analysis of microRNA-320a-related genes in osteoarthritis cartilage - Peng, Hao; Lin, Haibin (Frontiers in Surgery, 2023)
Osteoarthritis (OA) is one of the most common joint diseases worldwide. Many studies have shown that miRNA plays an important regulatory role in the pathological development of OA. We investigated microRNA-320a-related differentially expressed genes (DEGs) and pathways in OA by bioinformatic analysis. A total of 176 OA related miRNAs were searched and collected for enrichment analysis, and microRNA-320a was one of OA related miRNAs. Enrichment pathway and analysis of 1721 miRNA-320a-related target genes from MiRTarBase and TargetScan were performed using the online tools Metascape. And results shown that the biological processes were remarkably enriched in chromatin organization, cellular response to DNA damage stimuli, mRNA metabolic process, protein ubiquitination, and regulation of cell adhesion. And then we analysed miRNA-320a-targeted OA genes via KEGG, GO enrichment and Protein–Protein Interaction (PPI) Network. Our results showed that miRNA-320a played a role in OA through FoxO signaling pathway, PI3K-Akt signaling pathway, Focal adhesion, MAPK signaling pathway, HIF-1 signaling pathway and Cellular senescence. And we speculate that MAPK signaling pathway plays a key role in the effect of miRNA-320a on OA. Taken together, our study screened miRNA-320a-related genes and pathways in OA and, eventually, to improve the understanding of underlying mechanisms of miRNA-320a in OA.